PENGARUH LITERASI KEUANGAN, LITERASI AKUNTANSI, DAN LOCUS OF CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR DENGAN FINANCIAL SELF-EFFICACY SEBAGAI VARIABEL MEDIASI PADA PENGGUNA PAYLATER - Iqmaya, Adevia Sekar; Wulandari, Renny; Risal (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose – This study examines the effects of financial literacy, accounting literacy, and locus of control on financial management behavior among PayLater users, with financial self-efficacy as a mediating variable. Methods – A quantitative approach was employed using online questionnaire data from 130 active PayLater users in Indonesia via purposive sampling, analyzed through SEM-PLS in SmartPLS 4. Findings – Financial literacy (β = 0.348, p < 0.001) and locus of control (β = 0.196, p = 0.047) significantly influence financial management behavior, whereas accounting literacy does not (p = 0.734). Financial self-efficacy mediated only the locus of control–financial management behavior relationship (p = 0.045), not those involving financial literacy or accounting literacy. The model explains 51.7% of variance in financial management behavior. Research Implications – PayLater providers and regulators should prioritize practical financial literacy programs and features reinforcing users’ perceived control over credit obligations rather than formal accounting competencies. Originality – This study integrates financial literacy, accounting literacy, locus of control, and financial self-efficacy in a single model focused on PayLater users in the Indonesian digital credit context.